Religious experience and divinization in the sectarian Dead Sea scrolls: living in the liminal - Harris, Rebecca L. (Journal for the study of Judaism / Supplements, 2026)
"For members of the sectarian Dead Sea Scrolls movement, participation in the group would have granted an individual special privileges, including present, unmediated access to otherworldly realities. This understanding of the present as a type of liminal space is rooted in the group's constructions of time and space. Drawing on theories of liminality and anthropological research on religious consciousness, this study seeks to demonstrate how sectarian identity and ritual and liturgical practice might have cultivated an experience of present communion with divine beings that was also aspirational and aimed to achieve the human worshiper's permanent incorporation into the heavenly realm"-- Provided by publisher